Quality Of Health Services With Outpatient Satisfaction Level - Riszeki Fitria; Sri Sudarsih; Mohammad Qais Rezvani; Noor Fatima (CV Media Inti Teknologi, 2025)
Background of study: The increasing need for quality health center services, the service function needs to be improved to be more effective and efficient and provide satisfaction to patients and the community. Aims and scope of paper: This study aimed to determine the relationship between the quality of health services and the level of satisfaction of outpatients Methods: The design of this study used correlation analysis with a cross-sectional approach. The population in this study were all patients who had received health services totaling 142 people. The sampling technique of this study was consecutive sampling with a sample size of 44 people. The research instrument used a questionnaire. Data analysis used Spearman Rho. Result: The results of the study showed that almost all respondents considered the quality of service sufficient, namely 37 people (84.1%) and more than 50% of respondents were satisfied, namely 25 people (56.8%). The results of the Spearman Rho test showed a p value = 0.001 < α = 0.05 with a coefficient correlation value of 0.499, which means that there is a relationship between service quality and patient satisfaction. Conclusion: Semakin baik kualitas pelayanan, maka akan semakin puas pasien. Kualitas pelayanan yang baik memberikan dampak yang positif bagi kesembuhan pasien sesuai dengan hakekat pelayanan dasar dari pelayanan kesehatan adalah memenuhi kebutuhan dan pasien.